Role of PHOSPHO1 in Periodontal Development and Function. (July 2016) - Zweifler, L.E.; Ao, M.; Yadav, M.; Kuss, P.; Narisawa, S.; Kolli, T.N.; Wimer, H.F.; Farquharson, C.; Somerman, M.J.; Millán, J.L.; Foster, B.L.
The tooth root and periodontal apparatus, including the acellular and cellular cementum, periodontal ligament (PDL), and alveolar bone, are critical for tooth function. Cementum and bone mineralization is regulated by factors including enzymes and extracellular matrix proteins that promote or inhibit hydroxyapatite crystal growth. Orphan Phosphatase 1 ( Phospho1, PHOSPHO1) is a phosphatase expressed by chondrocytes, osteoblasts, and odontoblasts that functions in skeletal and dentin mineralization by initiating deposition of hydroxyapatite inside membrane-limited matrix vesicles. The role of PHOSPHO1 in periodontal formation remains unknown and we aimed to determine its functional importance in these tissues. We hypothesized that the enzyme would regulate proper mineralization of the periodontal apparatus. Spatiotemporal expression of PHOSPHO1 was mapped during periodontal development, and Phospho1 -/- mice were analyzed using histology, immunohistochemistry, in situ hybridization, radiography, and micro–computed tomography. The Phospho1 gene and PHOSPHO1 protein were expressed by active alveolar bone osteoblasts and cementoblasts during cellular cementum formation. In Phospho1 -/- mice, acellular cementum formation and mineralization were unaffected, whereas cellular cementum deposition increased although it displayed delayed mineralization and cementoid. Phospho1 -/- mice featured disturbances in alveolar bone mineralization, shown by accumulation of unmineralized osteoid matrix and interglobular patterns of protein deposition. Parallel to other skeletal sites, deposition of mineral-regulating protein osteopontin (OPN) was increased in alveolar bone in Phospho1 -/- mice. In contrast to the skeleton, genetic ablation of Spp1, the gene encoding OPN, did not ameliorate dentoalveolar defects in Phospho1 -/- mice. Despite alveolar bone mineralization defects, periodontal attachment and function appeared undisturbed in Phospho1 -/- mice, with normal PDL architecture and no evidence of bone loss over time. This study highlights the role of PHOSPHO1 in mineralization of alveolar bone and cellular cementum, further revealing that acellular cementum formation is not substantially regulated by PHOSPHO1 and likely does not rely on matrix vesicle–mediated initiation of mineralization.